2022
DOI: 10.1177/23259671221118561
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the Tibial Tubercle–Roman Arch Distance for Evaluating Tibial Tubercle Malposition and Predicting Patellar Dislocation via Magnetic Resonance Imaging

Abstract: Background: The tibial tubercle (TT)–trochlear groove (TT-TG) distance has low reproducibility in patients with a dysplastic trochlea, whereas the clinical value of the TT–posterior cruciate ligament (TT-PCL) distance remains controversial. Purposes: To establish a method to assess the position of the TT on magnetic resonance imaging (MRI) scans using the TT–Roman arch (TT-RA) distance, compare this method with the TT-TG and TT-PCL distance, and provide the pathological threshold value of the TT-RA distance in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…although the aim was to have the knee extended in the MRI scanner, the actual knee angle was not measured." 3 Could this be a glimpse that rotational issues might have a bearing in the threshold difference? Unfortunately, this was not investigated.…”
Section: Dear Editormentioning
confidence: 99%
“…although the aim was to have the knee extended in the MRI scanner, the actual knee angle was not measured." 3 Could this be a glimpse that rotational issues might have a bearing in the threshold difference? Unfortunately, this was not investigated.…”
Section: Dear Editormentioning
confidence: 99%
“…Therefore, the role of true tibial tubercle lateralization in the evaluation of patellar dislocation patients warrants further assessment. As mixed imaging tests, the TT-RA distance (AUC ¼ 0.8) and TT-TG distance (AUC ¼ 0.8) had higher capacity than TT-PCL distance (AUC ¼ 0.6) to distinguish patients with patellar dislocation from healthy individuals, 5,6 which indicate that the mixed imaging tests would be more suitable to evaluate patellar dislocation.As for the question of the accuracy of the TT-RA distance. We used the intraclass correlation coefficient to evaluate the precision of the measurements, and found that the TT-RA distance showed higher inter-and intraobserver reliability than the TT-TG distance (Table 2 of our study 6 ), especially in patients with patellar dislocation (Figure 6 of our study 6 ).…”
mentioning
confidence: 99%
“…Therefore, the role of true tibial tubercle lateralization in the evaluation of patellar dislocation patients warrants further assessment. As mixed imaging tests, the TT-RA distance (AUC ¼ 0.8) and TT-TG distance (AUC ¼ 0.8) had higher capacity than TT-PCL distance (AUC ¼ 0.6) to distinguish patients with patellar dislocation from healthy individuals, 5,6 which indicate that the mixed imaging tests would be more suitable to evaluate patellar dislocation.…”
mentioning
confidence: 99%
See 2 more Smart Citations